IMPROVING 3D SURFACE MEASUREMENT OF MECHANICAL DETAILS BY STRUCTURED LIGHT USING HIGH DYNAMIC RANGE - Tu (Journal of Military Science and Technology, 2021)
The measurement methods using structured light have the advantage of being fast, accurate, and noncontact with the surface of the object. However, these methods have reached its limitation when measuring mechanical details with high surface gloss, due to the unpredictable reflection of incident rays after reaching to object’s surface that, consequently, leads to the simultaneous appearance of several regions with different brightness. To address this problem, we proposed a method of synthesizing extended dynamic range images based on changing the exposure time of the camera and adjusting the illumination of the projector light source so that 3D point coordinates in both bright and dark areas could be obtained through the process. The dual-camera structured light experimental model and the lightcrafter 4500 projector are synchronized through the trigger, using the gray code in combination with the line-shift projection pattern. Experimental results show that the proposed method can precisely reconstruct the 3D surface of mechanical details, while providing higher performance than the state-of-the-art methods.